Penyebaran Fikih Mazhab Syafi’i di Nusantara: Studi Sosio-Historis Masa Kesultanan Palembang Darussalam - Adil, Muhammad; Harun, Muhamad (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
This study explains the spread of the Syafi'i school of fiqh in the Indonesian Archipelago by taking the time of the Palembang Darussalam Sultanate. The dissemination of the Syafi'i school of fiqh was officially carried out through the sultanate institution by the ulama appointed by the Sultan. The official positions in the field of religion are Pangeran Penghulu Nata Agama, Penghulu Nata Agama, and Khatib Imam. This position continued during the colonial period and ended until 1905 as Hoofd Penghulu. In addition, the dissemination of the Syafi'i school of fiqh was also carried out by scholars who had close ties to the sultanate, such as Abdul Samad al-Palimbani, Kemas Fakhruddin, and Syihabuddin al-Misri al-Jawi al-Palimbani. Authentic evidence of the spread of the Shafi'i School of jurisprudence occurred through the translation and copying movement of the Shafi'i School of Islamic scholars, as was done by Sheikh Abdul Samad who wrote and translated books written by Imam Ghazali in the fields of fiqh and Sufism, such as books of BidÄyat al-HidÄyah was translated as HidÄyat al-SÄlikÄ«n fÄ« Suluk al-Maslak al-MuttaqÄ«n, and IhyÄ 'UlÅ«m al-DÄ«n was translated as Sayr al-SÄlikÄ«n ilÄ IbÄdat Rabb al-AlamÄ«n. Thus, it can be seen that this model of dissemination has caused the Syafi'i school of jurisprudence to continue to experience its development until now to dominate as a school of law adopted by the community.